Ruthenium-catalysed dehydrogenative C–H borylation of arenes with pinacolborane. (1st July 2016) - Murata, Miki; Ueda, Yosuke; Hyogo, Mayu; Kohari, Yoshihito; Namikoshi, Takeshi; Watanabe, Shinji
A ruthenium complex prepared in situ from [RuCl2(p-cymene)]2 and TpMe2K [TpMe2 = hydrotris(3, 5-dimethylpyrazolyl)borate] is efficient for aromatic C–H borylation with pinacolborane (4, 4, 5, 5-tetramethyl-1, 3, 2-dioxaborolane). Arenes were borylated at more electron-rich positions. DFT calculations and kinetic isotope effect experiments suggest that the catalytic cycle should involve an electrophilic aromatic substitution with a borenium cation.